Kajian Pengaruh Bauran Pemasaran terhadap Penjualan di Prima In Hotel Malioboro - Ajie Wicaksono (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
The marketing mix has a vital role for tourism businesses such as hotels. The number of hotels in DIY reaches 96-star hotels and 589 non-star hotels. This study aims to determine the effect of the service promotion mix on sales at the Prima In Hotel Malioboro. This research is quantitative descriptive by taking data using a questionnaire/questionnaire to 100 respondents. Data analysis used linear regression with the help of the SPSS program. The results showed that the marketing mix carried out by the Prima In Hotel Malioboro has a positive and significant effect on sales (significance value 0.000 or p <0.05) with an effect of 73.7%. The structured linear regression equation is Y = 1.558 + 0.429 X which indicates that the marketing mix increases the sales. The marketing mix that affects sales includes advertising, sales promotion, publication, and personal selling. In contrast, sales that are influenced by the marketing mix include product aspects, service aspects, and management aspects.